Penerapan Latihan Skipping dan Jump Squat Terhadap Kualitas Jumping Smash Bola Voli - Muhammad Hanif Fatih; Nurhidayat Nurhidayat; Vera Septi Sistiasih (Jurnal Porkes, 2026)
The problem of low quality jumping smashes among volleyball extracurricular students at SMP Negeri 2 Gringsing, characterized by weak hits and suboptimal movement coordination, prompted this study. The purpose of this study was to analyze and compare the effectiveness of skipping exercises and jump squats in improving the quality of jumping smashes. The method used was quantitative with a quasi-experimental pretest-posttest two-group design. The sample consisted of 30 students who were randomly divided into the Skipping group (n=15) and the Jump Squat group (n=15), following 12 training sessions with a predetermined protocol. Data were collected using a valid and reliable jumping smash assessment rubric (α ≥ 0.70). Statistical analysis results showed that although both groups experienced improvement, skipping training produced a significantly higher average gain score (52.20) than Jump Squat (36.27) with a p-value of 0.032 and an effect size of d=0.83 (large category). The study concluded that Skipping training was more effective than Jump Squat in improving jumping smash quality, presumably due to the complexity of the neuromuscular stimulus and the resulting improvement in movement coordination. These findings can be considered in the development of training programs for beginner students.